The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter - Benoit Richard; Jean‐Luc Dupouey; Emmanuel Corcket; Didier Alard; Frédéric Archaux; Michaël Aubert; Vincent Boulanger; François Gillet; Estelle Langlois; Sébastien Macé; Pierre Montpied; Thérèse Beaufils; et al. (Global Ecology and Biogeography, 2021)
Aim Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location France. Time period 1995–2017. Taxa studied Vascular plants. Methods We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.

Reactions of Airway Epithelial Cells to Birch Pollen Grains Previously Exposed to In Situ Atmospheric Pb Concentrations: A Preliminary Assay of Allergenicity - Anne-Pauline Bellanger; Floriane Bosch-Cano; Laurence Millon; Pascale Ruffaldi; Marielle Franchi; Nadine Bernard (Biological Trace Element Research, 2012)

Orbital imprint on Holocene palaeohydrological variations in west‐central Europe as reflected by lake‐level changes at Cerin (Jura Mountains, eastern France) - Michel Magny; Gilles Bossuet; Pascale Ruffaldi; Aurélie Leroux; Jacques Mouthon (Journal of Quaternary Science, 2011)
This paper presents a lake‐level record for the Holocene at Lake Cerin (Jura Mountains, eastern France). It is based on a range of sedimentological techniques validated in previous studies, with a combination of systematic lithostratigraphic investigations of the infillings accumulated in the lacustrine basin, and sediment analyses of two selected cores. The chronology is based on 10 radiocarbon dates and pollen stratigraphy. On a millennial scale, the Cerin lake‐level record shows three distinct successive phases characterised by higher lake‐level conditions until ca. 9000 cal. a BP, followed by a maximal lowering at ca. 9000–8500 cal. a BP, and a progressive rise until the present. This rise was punctuated by centennial‐scale fluctuations, with major events around 4000, 2800 and after 1500 cal. a BP. Considered on a multimillennial scale, the general pattern of palaeohydrological changes reconstructed at Cerin reflects the impact of orbitally driven summer insolation. This is in agreement with other regional and extra‐regional palaeoclimatic records, although every record shows peculiarities in timing and shape depending on the proxy used for reconstruction. In this general context, centennial to multicentennial oscillations appear to have been second‐order events in comparison with the major influence of the orbital factor. Copyright © 2011 John Wiley & Sons, Ltd.

High‐resolution record of environmental changes and tephrochronological markers of the Last Glacial–Holocene transition at Lake Lautrey (Jura, France) - Boris Vannière; Gilles Bossuet; Anne‐Véronique Walter‐Simonnet; Pascale Ruffaldi; Thierry Adatte; Michel Rossy; Michel Magny (Journal of Quaternary Science, 2004)
This paper presents the results of a multiproxy investigation including volume magnetic susceptibility (κ), mineral and pollen analyses of Late Glacial sediments from Lake Lautrey (Jura, France). Small‐scale lithological variations have been identified with high stratigraphic resolution in order to establish lithostratigraphic correlations between cores. κ measurements, combined with mineralogical analyses, provide information on past sedimentary processes. This combined approach reflects major changes in terrestrial habitats and soil processes which may relate to the climatic events characterising the Late Glacial climatic warming and cooling phases. During warm intervals, the record indicates increased lake productivity via carbonate precipitation and decreased input of detrital material. In contrast, cooler intervals show reduced lake productivity, catchment area instability and increased detrital inputs. Several short interruptions in reforestation and in soil stabilisation can be identified and linked with abrupt colder events occurring through the Bølling. A general trend of warming is recorded from the coldest part of the Younger Dryas. Three tephra layers were also detected. The mineral composition analyses show that the upper tephra layer corresponds to the Laacher See eruption (Eifel, Germany) while the lower ones may relate to the volcanic activity of the Chaîne des Puys (Massif Central, France) around 13 000 cal. yr BP. These two events, recognised for the first time outside the Massif Central region, may provide additional chronostratigraphic markers for the Late Glacial sedimentary records of the Jura mountains and northern Alps. Copyright © 2004 John Wiley & Sons, Ltd.